2013
DOI: 10.1364/ol.38.000914
|View full text |Cite
|
Sign up to set email alerts
|

Electrodes for wide-bandwidth substrate-removed electro-optic modulators

Abstract: This Letter is on wide-bandwidth electrodes suitable for ultralow voltage substrate-removed compound semiconductor electro-optic modulators. Using a loaded line approach, traveling wave electrodes suitable for wide-bandwidth and low-voltage operation were studied theoretically and experimentally up to 35 GHz. Using staircase waveguides and n-i-p-i-n epilayer designs, electrode capacitance and resistance were reduced significantly. Experimental and modeling results are found to agree very well. Theoretical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This is mainly due to large device capacitance and the excessive resistance of p-layer. This difficulty can be solved using a so called staircase waveguide and an n-i-p-i-n epilayer design [16], [17]. Modulator electrodes fabricated this way demonstrated that modulation bandwidth in excess of 35 GHz is possible for 2-mm-long electrodes.…”
Section: Device Fabricationmentioning
confidence: 99%
“…This is mainly due to large device capacitance and the excessive resistance of p-layer. This difficulty can be solved using a so called staircase waveguide and an n-i-p-i-n epilayer design [16], [17]. Modulator electrodes fabricated this way demonstrated that modulation bandwidth in excess of 35 GHz is possible for 2-mm-long electrodes.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Fig. 3 shows the traveling wave electrode design utilizing loaded line approach [10], [11]. Unloaded part of the electrode is a coplanar transmission line on thick BCB over the transfer substrate.…”
Section: Traveling Wave Modulator Designsmentioning
confidence: 99%
“…We also made 2 V V π modulators with 1.8 mm long electrodes at 1.55 μm in InP using multi quantum well (MQW) cores [8]. Recently, we also published modulator designs with traveling wave electrodes suitable for wide bandwidth operation [9], [10]. All of this study is based on substrate removal technology in compound semiconductors.…”
mentioning
confidence: 99%